Effects of selenium, selenium‐enriched spirulina and phycocyanin on myocarditis stress parameters on LPS‐induced injury in H9c2 ventricular cardiomyoblasts - Thomas Castel; Karine Pichavant‐Rafini; Michaël Théron; Charlotte Gandubert; Karelle Léon (Physiological Reports)
Abstract Myocarditis is strongly represented in septic patients and is associated with a higher mortality rate. Spirulina platensis (Spi), a blue‐green algae, has anti‐inflammatory properties and can be enriched with selenium, an antioxidant essential oligoelement. In addition, phycocyanin (PC), a biliprotein extract from spirulina, displays interesting anti‐inflammatory and antiapoptotic effects. In this study, the objective was to determine the cardioprotective effects of Sodium selenite (Se), Spi, Spi + Se (SeSP) and PC on LPS‐induced inflammation, apoptosis, and oxidative stress parameters. H9c2 cells were co‐treated with or without LPS (5 μg/mL) and Se (0.5 μM), Spi (2.5 μg/mL), SeSP (0.5 μM Se + 2.5 μg/mL Spi) and PC (0.1 μg/mL) for 24 h. Inflammation was investigated by measurement of NFκB activation, IL‐6, and caspase 1 expression, while apoptosis was measured by Bax, Bcl‐2, and caspase‐3 expression. Furthermore, GPx and SOD activities were analyzed, as well as isoprostanes and nrf‐2 expression. Activation of MAPK Junk and p38 was also determined. Our results demonstrated that Se could only reduce p65 S536 phosphorylation. SeSP could limit Bax expression, while an increase in IL‐6 was detected without LPS. Moreover, PC could reduce IL‐6 and Caspase‐1 expression and could have promising properties to decrease LPS‐induced myocarditis outcomes.